8. HISTOPATHOLOGICAL CHARACTERISTICS OF EPILEPTIC LESIONS SURGERYED AT VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Background: Epilepsy is one of the most common and serious neurological disorders worldwide, with an increasing burden and affecting nearly all age groups. Histopathological examination after epilepsy surgery plays an important role in determining the cause of epilepsy, guiding treatment, and providing essential information for research into epileptogenic mechanisms and the development of new therapeutic approaches.Objective: To evaluate histopathological lesions in patients undergoing epilepsy surgery and several clinical characteristics.Subjects and methods: A cross-sectional descriptive study on 46 patients who underwent epilepsy surgery and histopathological examination at the Department of Pathology, Viet Duc University Hospital, from January 2024 to December 2024.Results: The mean age of the study group was 21.98 ± 9.381 years, with a male-to-female ratio of 1.7. The proportion of seizures with and without aura was 41.3% and 58.7%, respectively. All patients presented with focal seizures. The most common symptoms were sudden loss of consciousness (93.5%), early eye or head deviation (47.8%), and automatisms (45.7%). Hippocampal sclerosis accounted for 30.4%, focal cortical dysplasia for 19.6%, glioma for 23.9%, and dysembryoplastic neuroepithelial tumor for 4.3%. Hippocampal sclerosis combined with focal cortical dysplasia accounted for 13%, hippocampal sclerosis combined with Glioma for 6.5%, and hippocampal sclerosis combined with dysembryoplastic neuroepithelial tumor for 2.2%.Conclusion: Epilepsy can onset at any age but tends to be more prevalent in the younger age group from 10 to 29 years, with no gender difference. The most common clinical seizure type is focal impaired awareness seizure. The most frequent histopathological findings are hippocampal sclerosis and focal cortical dysplasia.
Keywords: Epilepsy; hippocampal sclerosis; focal cortical dysplasia; epilepsy histopathology.